2012
DOI: 10.1074/jbc.m112.377606
|View full text |Cite
|
Sign up to set email alerts
|

Probing Conformational Changes in Human DNA Topoisomerase IIα by Pulsed Alkylation Mass Spectrometry

Abstract: Background:The catalytic cycle of Top2 has multiple steps of reactions with corresponding conformational changes. Results: We can monitor conformational dynamics of hsTop2␣ upon binding with cofactors and the inhibitor ICRF-193. Conclusion: Coordinated movements of the N-gate and DNA gate of hsTop2␣ occur with binding to cofactors and an inhibitor. Significance: Structural dynamics of hsTop2␣ can be detected during key catalytic steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Since (−)-xanthatin contains an exo -methylene lactone group as a possible reactive electrophilic moiety (Zhang et al, 2005; Ghantous et al, 2010; Takeda et al, 2011), and since Topo IIα activity is sensitive to –SH alkylation (via Michael addition with alkylating agents) (Jensen et al, 2002; Wang et al, 2001; Chen et al, 2012), we reasoned that (−)-xanthatin may function in its activity through an –SH reactor mechanism. We tested whether additions of the –SH-containing agents, NAC or dithiothreitol (DTT), would block the Topo IIα inhibitory activity elicited by (−)-xanthatin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since (−)-xanthatin contains an exo -methylene lactone group as a possible reactive electrophilic moiety (Zhang et al, 2005; Ghantous et al, 2010; Takeda et al, 2011), and since Topo IIα activity is sensitive to –SH alkylation (via Michael addition with alkylating agents) (Jensen et al, 2002; Wang et al, 2001; Chen et al, 2012), we reasoned that (−)-xanthatin may function in its activity through an –SH reactor mechanism. We tested whether additions of the –SH-containing agents, NAC or dithiothreitol (DTT), would block the Topo IIα inhibitory activity elicited by (−)-xanthatin.…”
Section: Resultsmentioning
confidence: 99%
“…Topo II poisons, such as etoposide, stabilize the Topo II-DNA covalent cleavage complex leading to an accumulation of DNA double-strand breaks (i.e., linear DNA), whereas agents that inhibit the enzyme during other reaction steps are designated as catalytic inhibitors (Larsen et al, 2003a). Several studies have shown that Topo IIα catalytic activity is sensitive to thiol (–SH)-reactive agents such as maleimide, orthoquinone, cisplatin, and other quinones, leading to an inactivation of the enzyme via interactions with cysteine residues (Wang et al, 2001; Jensen et al, 2002; Lu et al, 2005; Chen et al, 2012). The Topo IIα monomer contains 13 cysteine residues and at least five of these cysteines are present principally as reduced free –SH groups (Hasinoff et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Solvent-accessible cysteine side chains are susceptible to alkylation by monobromobimane (mBBr), which reacts with free thiols to produce a covalent adduct (18). We used this reaction, in combination with mass spectrometry, to determine the effect of H3K4me3 binding on the distribution of solvent-exposed cysteine thiols in RAG.…”
Section: Resultsmentioning
confidence: 99%
“…Pulse alkylation was based on a published procedure (18). The protocol is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation